Study of Microheterogeneity in Acetonitrile–Water Binary Mixtures by using Polarity‐Resolved Solvation Dynamics. Issue 16 (25th September 2015) - Koley, Somnath; Ghosh, Subhadip
Abstract: The solvation dynamics of three coumarin dyes with widely varying polarities were studied in acetonitrile–water (ACN–H2 O) mixtures across the entire composition range. At low ACN concentrations [ACN mole fractions ( X ACN )≤0.1], the solvation dynamics are fast (<40 ps), indicating a nearly homogeneous environment. This fast region is followed by a sudden retardation of the average solvation time (230–1120 ps) at higher ACN concentrations ( X ACN ≈0.2), thus indicating the onset of nonideality within the mixture that continues until X ACN ≈0.8. This nonideality regime ( X ACN ≈0.2–0.8) comprises of multiple dye‐dependent anomalous regions. At very high ACN concentrations ( X ACN ≈0.8–1), the ACN–H2 O mixtures regain homogeneity, with faster solvation times. The source of the inherent nonideality of the ACN–H2 O mixtures is a subject of debate. However, a careful examination of the widths of time‐resolved emission spectra shows that the origin of the slow dynamics may be due to the diffusion of polar solvent molecules into the first solvation shell of the excited coumarin dipole. Abstract : What a mix ! The solvation dynamics of three coumarin dyes with various polarities were studied in acetonitrile–water (ACN–H2 O) mixtures. Mixtures with ACN mole fractions between 0.2 and 0.8 show unexpectedly slow solvation times. The source of this nonideality is studied by time‐resolved emission spectroscopy and is revealed to be the diffusion of polar solvent molecules into the first solvation shell of the excited coumarin dipole.